2005
DOI: 10.1056/nejmoa050893
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Osteoprotegerin for Juvenile Paget's Disease

Abstract: Juvenile Paget's disease, a genetic bone disease characterized by accelerated bone turnover, results from inactivating mutations in the gene encoding osteoprotegerin--a key regulator of osteoclastogenesis. The effects of recombinant osteoprotegerin were investigated in two adult siblings with juvenile Paget's disease. Bone resorption (assessed by N-telopeptide excretion) was suppressed by once-weekly subcutaneous doses of 0.3 to 0.4 mg per kilogram of body weight. After 15 months of treatment, radial bone mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 15 publications
0
33
0
2
Order By: Relevance
“…Other studies have shown that increased bone metabolism may be associated with TNFRSF11B sequence variants which downregulate or block the expression of the osteoprotegerin gene [22, 23]. In a recent paper, Xue et al [24] showed that OPG serum levels were significantly higher in patients with intervertebral disc degeneration and the TC or CC genotype at the c.- 223C > T polymorphic locus (rs2073617) than those carrying the wild-type homozygous (TT) genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that increased bone metabolism may be associated with TNFRSF11B sequence variants which downregulate or block the expression of the osteoprotegerin gene [22, 23]. In a recent paper, Xue et al [24] showed that OPG serum levels were significantly higher in patients with intervertebral disc degeneration and the TC or CC genotype at the c.- 223C > T polymorphic locus (rs2073617) than those carrying the wild-type homozygous (TT) genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Mice lacking functional osteoprotegerin show growth plate abnormalities (12). In humans, inactivating mutations of the gene encoding osteoprotegerin result in juvenile Paget's disease, which is primarily characterized by excessive bone resorption but also causes short stature (13). Secreted frizzled-related protein 4 inhibits action of the Wnt system (14), which is critical for normal growth plate function (15,16).…”
mentioning
confidence: 99%
“…The effect of recombinant osteoprotegerin was studied in patients with juvenile Paget's disease (33). This disease is characterized by an accelerated bone turnover due to inactivating mutations in the gene encoding osteoprotegerin.…”
Section: Recent Advancesmentioning
confidence: 99%